Health Co-benefits of Climate Change Mitigation Action - Verica Taseska-Gjorgievska; Aleksandar Dedinec; Natasa Markovska (Journal of Sustainable Development of Energy, Water and Environment Systems)

(untitled)
Addressing the potential health benefits of climate change mitigation action, this study uses the Carbon Reduction Benefits on Health tool and the MARket ALlocation model to evaluate the health co-benefits of the proposed energy sector policies and measures in North Macedonia’s enhanced nationally determined contribution. The study hypothesises that implementing these policies and measures will significantly reduce morbidity and mortality due to air pollution by 2030. The results indicate 629 prevented bronchitis cases, 2,788 fewer asthma symptom days among children, and 143 preventable deaths, leading to considerable welfare improvements and economic savings. The findings underscore the importance of considering health outcomes in climate policy decisions, emphasising the substantial public health benefits alongside climate gains, as an incentive for emissions reduction. Sharing these findings with other countries will enhance efforts to limit the global temperature rise well below 2˚C by the century’s end.